Enhancing Instant Fortified Rice Congee (IFRC) for Elderly Nutrition: Collagen and Curcumin Optimisation Using Response Surface Methodology (RSM) - Mohd Shaharom, Noor Farisya; Ab Mutalib, Siti Roha; Yusoff, Anida; Seow, Eng Keng (Indonesian Food Science and Technology Journal, 2024)
Instant rice congee (IRC) fortified with functional ingredients has been specifically formulated to provide enhanced nutrition for the elderly. The optimisation of collagen and curcumin amounts in instant fortified rice congee (IFRC) was determined using Response Surface Methodology (RSM). The study revealed that the optimal conditions for IFRC formulation involved incorporating 7.96 g of collagen and 361 mg of curcumin, resulting in the highest observed values for protein content (32.41%), Total Phenolic Content (TPC) at 24.75 mg GAE/g sample, Ferric Reducing Antioxidant Power (FRAP) at 6.03 mg TE/g sample, adhesiveness at -329.23 g/s and cohesiveness at 0.60. In contrast, the formulation exhibited the lowest values for hardness (581.70 g). These findings, derived from the application of RSM, provide valuable insights into the optimal combination of collagen and curcumin in IFRC, showcasing its potential to enhance key nutritional and textural attributes. The outcomes from this study offer practical guidance for utilising collagen and curcumin as functional ingredients in fortified foods, particularly in the context of creating nutritionally enriched and palatable options for the elderly.